The Role of Toxic Leadership and Exclusion in The Workplace Against Intention to Leave Work With Psychological Distress as A Mediator And Gratitude as A Moderator - Pramudya, Thalia Altamilano; Rostiana, Rostiana; Budiana, I Made (Eduvest - Journal of Universal Studies, 2025)
This research investigates the impact of toxic leadership and workplace ostracism on employees' intentions to leave their jobs, with psychological distress as a mediator and gratitude as a moderator. Job turnover intention refers to an employee's desire to permanently quit their job, influenced by factors such as toxic leadership—characterized by authoritarian and unpredictable behavior—and ostracism, where individuals are ignored by colleagues. Both toxic leadership and ostracism can lead to psychological distress, which encompasses stress and emotional discomfort affecting mental well-being. Conversely, high levels of gratitude may mitigate the intention to leave. Utilizing an explanatory research design with a quantitative approach, the study employed five measurement instruments: a turnover intention questionnaire, a toxic leadership questionnaire, a workplace ostracism questionnaire, a psychological distress questionnaire, and a gratitude questionnaire. Conducted across three construction companies in West Jakarta, the study involved a sample of 150 employees. Findings indicate that toxic leadership and ostracism predict employees' turnover intentions, mediated by psychological distress. However, gratitude was not found to moderate the relationship between psychological distress and turnover intention in this model. The research highlights the importance of addressing toxic leadership and ostracism to reduce turnover intentions by developing improved policies and interventions that alleviate psychological distress among employees.